The relationship between work family conflict and work satisfaction among single parent employees in Yogyakarta - Putra, Eggy Mahendra; Yuniasanti, Reny; Fitriana, Nina; Hutagalung, Fonny Dameaty (Insight: Jurnal Ilmiah Psikologi, 2022)
The demands and pressures experienced by a single parent both from family and work can affect the level of work satisfaction. This can lead to work family conflict that occurs because of an imbalance between the role of a worker and the role of a family member. This research aims to determine the relationship between work family conflict and work satisfaction among single parent employees in Yogyakarta. The subjects of this research are 60 single parent employees. Purposive sampling were applied in this current research as the sampling technique. This research used two scales, namely work satisfaction scale (22 items; α = 0,853) and work family conflict scale (16 items; ; α = 0,810). Based on the results of the product moment correlation analysis, it was found that there was a significant relationship between work family conflict and work satisfaction (rxy) = -0.788 and p = 0.000. The higher the work family conflict, the lower the work satisfaction and conversely. The lower the work family conflict, the higher the work satisfaction among single parent employees. The value of the coefficient of determination (R2)  is 0.621 which indicates that the work family conflict variable provides an effective contribution of 62.1% to work satisfaction and the rest is influenced by other factors.